Mandibular Fracture Severity and Patient Health Status Are Associated With Postoperative Inflammatory Complications - Gordon, Paul E.; Lawler, Matthew E.; Kaban, Leonard B.; Dodson, Thomas B. (Journal of oral and maxillofacial surgery, 2011)
To identify risk factors associated with postoperative inflammatory complications (POICs) after treatment of mandibular fractures. The investigators designed a case–control study and enrolled a sample of patients treated for mandibular fractures at Massachusetts General Hospital between August 2004 and January 2010. Subjects who developed POICs after fracture management were categorized as cases. A POIC was defined as 1) recurrent swelling, fever, increased pain, or trismus; 2) wound dehiscence with purulent drainage; 3) exposed or infected hardware; 4) abscess formation; 5) radiographic evidence of osteomyelitis; and/or 6) presence of a fistula. Controls had no complications. For each case, 2 controls were selected. Predictor variables were categorized into the following sets: demographic, fracture-specific, and perioperative. Bivariate and multiple logistic regression analyses were used to identify factors associated with POICs. During the study interval, 575 subjects with mandible fractures were evaluated and treated. The study sample consisted of 44 cases and 88 controls. In the multiple regression model, an increasing Mandibular Injury Severity Score (odds ratio = 1.4; 95% confidence interval 1.2-1.6) and a positive medical history (odds ratio = 1.4; 95% confidence interval 1.03-1.8) were significantly ( P < .05) associated with an increased risk for a POIC. Fracture severity assessed using the Mandibular Injury Severity Score and pre-existing medical problems were associated with increased risk for postoperative inflammatory complications following treatment of mandibular fractures.